PANDANGAN ISLAM TERKAIT GAYA HIDUP HEDONISME PADA GENERASI Z - Herlina, Erna Rika (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
Hedonism is a view of life that assumes a person will feel happy if it is done by seeking pleasure or happiness as much as possible. This research is motivated by an attitude or lifestyle of hedonism which states that pleasure is here to be enjoyed and is the purpose of human life in this world. At first only certain people could have this hedonistic attitude and lifestyle, considering that to carry out this hedonistic attitude it required a lot of funds to be spent. However, in the end this attitude has spread to people from other circles even though they are in poor living conditions. At this time the hedonism lifestyle is mostly practiced by generation z because it is considered a pride to have this hedonistic lifestyle. Islam certainly strongly rejects this hedonistic attitude as a form of prohibition from extravagant and extravagant attitudes. Islam teaches that life is better if lived with simplicity. According to the view of Islam as a Muslim should use his wealth for useful things and not used for useless things. Â Keywords: lifestyle, hedonism, generation z, Islamic view